PENINGKATAN KETRAMPILAN MENJADI IDE USAHA - Andreas Sarjono; Maria Josephine Tyra; Catharina Clara; Ega Leovani; Lina (Universitas katolik Musi Charitas, 2017)
This public service activity was executedto generate the excitement of housewifes to improve the household economics condition. It is believed that everyone was their own strength for instance the ability in cooking, making crafts, gardening, and so on. But many people do not realize that those could be developed to reach better life. The method is in the form of counselling about the importance of housewif’s role in improving the household economic condition, skills, followed by training in designing appropriate business in accordance with their capabilities and skills. It includes the examples of creative products that can be practiced by housewifesbased on their talent and interests.